2010
DOI: 10.4314/ajtcam.v6i3.57175
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and use of alternative medical therapy amongst urban residents of Osun state, southwestern Nigeria

Abstract: Alternate medicine which has a long history has been relegated to the background by the evolution of modern medicine. In recent times, however, alternative medical therapy has been growing in popularity and getting increasing attention and interest. This study assessed the knowledge, attitude and use by urban dwellers of alternative medical therapies. This was a cross-sectional descriptive study which used a semi-structured questionnaire to gather information from 812 randomly selected urban respondents. Major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 14 publications
4
46
3
Order By: Relevance
“…The agbo (concoction) which was the mostly used herbal remedies by pregnant women in this study was consistent with the findings of Fakeye, Adisa & Ismail [27] and Bamidele, Adebimpe & Oladele [5] in their studies conducted in Nigeria. They conclude that more than two-third of respondents had used herbal medicines in crude forms or as pharmaceutical prepackaged dosage forms, with a high percentage preferring self-prepared formulated concoction (agbo).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The agbo (concoction) which was the mostly used herbal remedies by pregnant women in this study was consistent with the findings of Fakeye, Adisa & Ismail [27] and Bamidele, Adebimpe & Oladele [5] in their studies conducted in Nigeria. They conclude that more than two-third of respondents had used herbal medicines in crude forms or as pharmaceutical prepackaged dosage forms, with a high percentage preferring self-prepared formulated concoction (agbo).…”
Section: Discussionsupporting
confidence: 81%
“…Also the high usage of herbs among rural women in this study contradicted the findings of Louik, Gardiner & Kelley, et al [32] who reported low usage (5.8%) among their respondents but at par with the findings of Bamidele, Adebimpe & Oladele [5] who reported similar findings among urban respondents in Nigeria. The preference for herbal remedies by pregnant women in this study over orthodox medicine could be linked with the submission of Elujoba, Odeleye and Ogunyemi [10] that alternative medicine is intrinsically interwoven with the culture of the people -a socioeconomic and sociocultural heritage.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Teshome-Bahiru (2006) reported that the process of urbanisation has greatly impacted on the use of traditional medicine in both rural and urban communities of Addis Ababa, Ethiopia, in both positive and negative ways. The introduction of Western culture particularly into rural parts of Africa has had a tremendous negative impact on the role traditional medicine plays and as Western education, Christianity and increased contact with the global community become an integral part of rural communities, taboos, traditions and customs have been affected and in some instances abandoned altogether These challenges notwithstanding, there is increasing evidence that traditional medicine continues to hold sway in both rural and urban communities of Africa even when modern health care facilities are available to meet wide range of health care needs (Sheriffs,1996;De Jong,1991;Bamidele, 2009, Eduards, 1986. De Jong (1991) has reported that even educated people in urban cities still consult TH whose demand for services are high, as they are perceived to be skilled to help people cope with psychological and social problems associated with illness and disease.…”
Section: Continued Existence Of Tm and Oral Health Seeking Behaviour mentioning
confidence: 99%